How can the process of transforming Islamic texts into practice be explained integratively through the perspective of reading comprehension, interpretation, fiqh, and the history of Islamic culture? - Yasnel Yasnel; Zulhidah Zulhidah; Herlina Herlina; Syarifuddin Syarif; Andi Murniati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
The transformation of Islamic texts into religious practice is a significant issue in contemporary Islamic studies due to the separation of cognitive, interpretive, normative, and socio-cultural approaches. Existing studies often discuss reading comprehension, interpretation, fiqh, and Islamic cultural history independently, leaving the stages of text transformation insufficiently explained. This study aims to develop an integrative understanding of how Islamic texts become religious practices through the synthesis of these four perspectives. Using a Systematic Literature Network Analysis (SLNA) approach, the study analyzed indexed scientific articles from the Scopus database. From 2,550 initial findings, 18 articles met the inclusion criteria after systematic filtering. Bibliographic data were analyzed using VOSviewer to map keyword co-occurrence networks and thematic clusters, while RStudio bibliometric packages were used for descriptive and publication pattern analyses. The findings reveal that transformation occurs in a layered and non-linear process, beginning with cognitive text comprehension, followed by interpretation, institutionalization in fiqh, and materialization into lived religious practices influenced by historical and cultural contexts. The study also identifies an epistemological gap caused by the absence of an integrative model connecting these stages systematically. As a contribution, this research proposes an integrative conceptual model linking text, meaning, authority, and practice in Islam.